Lessons learned from more than a decade of greenhouse gas flux measurements at boreal forests in eastern Siberia and interior Alaska - Hiyama, Tetsuya; Ueyama, Masahito; Kotani, Ayumi; Iwata, Hiroki; Nakai, Taro; Okamura, Mikita; Ohta, Takeshi; Harazono, Yoshinobu; Petrov, Roman E.; Maximov, Trofim C. (Polar Science, 2021)
We summarized our recently-published papers on greenhouse gas exchanges at two important boreal regions underlain by permafrost: eastern Siberia and interior Alaska. Relevant literatures were also referred to, and future research directions on the high-latitude terrestrial processes were suggested. Long-term monitoring of CO2 fluxes at the boreal forests revealed that anomalous weather and disturbances changed the CO2 balance. More than a decade is required to return to a CO2 sink at burned forests in interior Alaska. Anomalous high precipitation altered the forest structure in eastern Siberia, shifting the overstory/understory contributions to the CO2 balance. The CH4 emissions were higher in the two boreal forests than in the other boreal forests. Upscaling the in-situ observations and comparisons with top-down approaches revealed considerable inconsistencies exist among the approaches. We recommend the following directions in future research. First, long-term monitoring is indispensable to detect the effect of climate change on ecosystems. Second, disturbance impacts, including fire, thermokarst, and wet spells, need to be quantified. Third, further observations are necessary for constraining CH4 exchange models. Finally, reconciling top-down and bottom-up approaches is required to reduce uncertainty. Prompt sharing of observed data and model products is crucial to improve our understanding of high-latitude processes. journal article